Ubiquitous and pervasive knowledge and learning management semantics, social networking and new media to their full potential - Lytras, Miltiadis D. 1973-; Naeve, Ambjorn (Idea Group Pub., 2007)
"This book presents an alternative view to ubiquitous and pervasive knowledge, architectural frameworks, and methodological issues, and introduces some of the major techniques and tools developed in the domain of ontology building, analysis, and semantic Web"--Provided by publisher.